The Use of Google Classroom in Learning Writing Descriptive Text: Students’ Gifted Perceptions - Sri Hartati; Syarfuni Syarfuni; Siti Mayang Sari (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
English is one of the essential language skills for language learning. reading is considered important because it's one of the communication mediums, and it makes students critical. However, writing is a significant difficulty for both native and non-native learners. Due to advancements in technology, Google Classroom enables educators and students to communicate and engage in new ways. Google Classroom, being one of the most widely used LMS platforms, may assist students in developing their ability to write descriptive text. This research aimed to investigate students’ perception of using Google Classroom in learning writing descriptive text. The subject examined students in the fifth grade at a Elementary school. This research used a qualitative approach with a narrative inquiry. The researcher utilized semi-structured interviews to gather the data and analysed them using the thematic analysis of Braun & Clarke. The study discovered that students preferred using Google Classroom to learn the descriptive text. Google Classroom helps them to know and understand teaching materials easily. However, Effort Expectancy may be altered with sufficient internet use and Google Classroom